PENGARUH ALOKASI BELANJA MODAL, DESENTRALISASI FISKAL, DAN KINERJA KEUANGAN DAERAH TERHADAP KEMISKINAN DIMEDIASI INDEKS PEMBANGUNAN MANUSIA KABUPATEN SRAGEN TAHUN 2011-2020 - Fitasari, Kristina (Fakultas Ekonomi, Universitas Sanata Dharma Yogyakarta, 2023)
Poverty is a problem for both developed and developing countries. Poverty is determined by the level of income and the ability of a country to meet its most basic needs. In addition, the factor that affects poverty is the human development index called fiscal decentralization. This study aims to describe the allocation of expenditures, fiscal decentralization, and financial performance of capital in the Sragen Regency to poverty. The research method in this study is descriptive quantitative, collecting information to test hypotheses or answer questions through questionnaires. The results obtained in this study showed a significant positive relationship between the allocation of capital expenditure in the Sragen district, a significant positive relationship between fiscal decentralization on poverty, and no significant or negative relationship between the development index on poverty.